2004
DOI: 10.1189/jlb.1203648
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide receptor P2X7 mediates actin reorganization and membrane blebbing in RAW 264.7 macrophages via p38 MAP kinase and Rho

Abstract: Extracellular nucleotides regulate macrophage function via P2X nucleotide receptors that form ligand-gated ion channels. In particular, P2X7 activation is characterized by pore formation, membrane blebbing, and cytokine release. P2X7 is also linked to mitogen-activated protein kinases (MAPK) and Rho-dependent pathways, which are known to affect cytoskeletal structure in other systems. As cytoskeletal function is critical for macrophage behavior, we have tested the importance of these pathways in actin filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 54 publications
7
120
0
1
Order By: Relevance
“…Disruption of actin filaments by cytochalasin D, which inhibits actin polymerization and depolymerization, diminished the P2X7R-induced blebbing without affecting the receptor's ionotropic function. Activation of Rho and p38 MAPKs occurred concurrently with P2X7R-induced membrane blebbing [46]. Likewise, pharmacological inhibitors of p38, Rho, and Rho kinases all reduced P2X7R-stimulated actin reorganization as well as the blebbing [44,46,47].…”
Section: P2x7r Regulation Of Plasma Membrane Blebbingmentioning
confidence: 87%
See 1 more Smart Citation
“…Disruption of actin filaments by cytochalasin D, which inhibits actin polymerization and depolymerization, diminished the P2X7R-induced blebbing without affecting the receptor's ionotropic function. Activation of Rho and p38 MAPKs occurred concurrently with P2X7R-induced membrane blebbing [46]. Likewise, pharmacological inhibitors of p38, Rho, and Rho kinases all reduced P2X7R-stimulated actin reorganization as well as the blebbing [44,46,47].…”
Section: P2x7r Regulation Of Plasma Membrane Blebbingmentioning
confidence: 87%
“…Studies with different cell types have indicated that P2X7R-stimulated membrane blebbing appears to involve several common signaling pathways [44,45]. ATP-induced membrane blebbing was found to be concurrent with actin reorganization in murine macrophages [46] and could be dissociated from the non-classical release of mature IL-1ÎČ that is also stimulated in parallel by P2X7R in such macrophages [47]. Disruption of actin filaments by cytochalasin D, which inhibits actin polymerization and depolymerization, diminished the P2X7R-induced blebbing without affecting the receptor's ionotropic function.…”
Section: P2x7r Regulation Of Plasma Membrane Blebbingmentioning
confidence: 91%
“…This suggests that P2X7-dependent signaling contributes to restricting lamellipodia broadening. It is known that activation of P2X7 receptor causes activation of Rho kinase [32,33]. Therefore, blockade of P2X7 receptor would suppress activation of the Rho pathway and result in aberrant activation of Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…Although P2X 7 has been reported to cause caspase, MAP kinase or Rho/ROCK protein activation [20,21,22], ion fluxes are still thought to be the most important signal transduction device associated to P2X 7 . Uncontrolled Na + and Ca 2+ entry is the main trigger of the well-known P2X 7 -dependent cytotoxicity, while K + efflux is thought to be the main mechanism by which P2X 7 drives pro-IL-1ÎČ processing.…”
Section: The Biochemical Basis Of P2x 7 -Mediated Growth Stimulationmentioning
confidence: 99%